Covid-19 in liver transplant recipients: A national cohort - Kabaçam, Gökhan; Turan, İlker; Kıyıcı, Murat; Melekoğlu Ellik, Zeynep; Dolu, Süleyman; Dayangaç, Murat; Arı, Derya; Turan Gökçe, Dilara; Yıldırım, Abdullah Emre; Gençdal, Genco; Harputluoğlu, Murat; Kartal, Aysun; et al. (Elsevier, 2021)
Introduction: The effect of coronavirus disease 2019 (COVID-19) on outcomes of liver transplant recipients is not known very well. Aim: Methods The aim of the present study was to describe the early outcomes of liver transplant recipients with COVID-19.
Keywords: Liver Transplant; Covid-19; Recipients